BOOK REVIEW OF WUTHERING HEIGHTS WRITTEN BY EMILY BRONTË - Herawati, Septian (LANTERN (Journal on English Language, Culture and Literature), 2015)
Nobody is perfect. Human being is full of characteristics. They have both good and evil characters. In this life, sometimes people meet someone with friendly, humble and good personality. However, there are also people who meet the opposite, such us sadistic, vengeful and cruel personality. These human characteristics can easily be found not only in real life, but also in literary works as reflected in novel Wuthering Heights. Wellek and Warren stated that “literature represents life and life is, in large measure, a social reality even though the natural world and the inner or subjective world of the individual have also been objects of literary imitation (1973:94).” This statement means that literary works are imitation of the real life since they include and reflect human life. There is a close relationship between the world where an author lives and the literary works which they produce. The authors will show their opinion toward reality, phenomenon and situation around them in literary works, so this is why literary works portray the life of society and the authors. The portrait may be formed in character, plot, setting, and etc.